Factors Associated with Mothers’ Interest in Choosing Intrauterine Contraceptive Device (IUD) at Moti Health Center, Ternate City, North Maluku Province - Nirmalasari, Sartika; Ratna Dwi Jayanti; Farizi, Sofia Al; Utomo, Budi (Journal of Ners and Midwifery, 2025)
The utilization of intrauterine devices (IUDs) remains low in Maluku Province, with a reported adoption rate of only 33.9% in 2020. At the Moti Community Health Center in 2022, IUD usage was recorded at just 0.19%. This study aimed to identify factors influencing the interest in choosing IUD at the   Moti Community Health Center in Ternate City, North Maluku Province. Using a quantitative cross-sectional design, the research employed multistage random sampling involving 66 women of reproductive age (WRA). Data collection utilized questionnaires and interviews, with statistical analysis including univariate and bivariate analyses using Chi-Square tests. Out of 66 respondents, 19 (28.8%) expressed interest in choosing IUD, while 47 (71.2%) did not. Chi-square analysis revealed significant correlations between interest in IUD and variables such as knowledge (p-value 0.002), attitude (p-value 0.031), education (p-value 0.027), husband's support (p-value 0.000), and acceptance of birth control information (p-value 0.001). However, parity showed no significant association (p-value 0.624) with mothers' interest in choosing IUD at the Moti Health Center in Ternate City, North Maluku Province. Significant relationships were observed for variables like knowledge and attitude, whereas parity did not demonstrate a notable link. Increasing IUD adoption among WRA requires enhanced education, family involvement, flexible services, and competent healthcare providers. Encouraging husbands’ participation, structured counselling, home visits, and incentives can boost uptake. These findings highlight the need for training the staff, and collaborating with community leaders to increase IUD adoption.